Alaqah Al-Kafa'ah As-Syakhsyiyah Li Al-Mu'allimin Ala Ihtimam Ta'allum Al-Lugah Al-Arabiyah Lada Tullab Al-Madrasah Ats-Tsanawiyah Al-Ahliyah Ira Medan - Nurfasilah, Nurfasilah; Zulheddi, Zulheddi (LPPM Universitas KH.A. Wahab Hasbullah, 2025)
This study aims to examine the relationship between the personality of Arabic language teachers and students’ interest in learning Arabic. The research employs a quantitative method with a correlational approach. The population consists of all students at MTs Ira Medan, with a sample of 28 students selected through random sampling. Data were collected using a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Pearson Product Moment correlation formula. The results indicate a statistically significant relationship between teacher personality and students’ learning interest, with a significance value of 0.00 (p < 0.05) and a correlation coefficient of 0.669, which falls into the strong category (0.61–0.80). This value exceeds the r table (0.374), leading to the conclusion that there is a strong positive relationship between teacher personality (X) and students’ interest in learning (Y), with a contribution of 44.7%. These findings highlight the importance of teacher personality development as a key factor in enhancing students' interest in learning Arabic.